Comparison study between open-loop and closed-loop identification for industrial hydraulics actuator system - Ghazali, Rozaimi; Mohamad Ali, Nur Husnina; Jaafar, Hazriq Izzuan; Ghani, Muhammad Fadli; Chong, Chee Soon; Has, Zulfatman (International Journal Of Mechanical Engineering And Robotics Research (IJMERR), 2024)
In control applications involving motion control, precise control of the Industrial Hydraulics Actuator (IHA) is necessary to accurately assess the position of the actuator rod. Non-recursive identification is used to model the system with an open-loop and closed-loop approach for this paper. The grey box approach is used to estimate the continuous model and parameter estimation for the system. The System Identification toolbox in MATLAB is used for the model estimation. The process starts by obtaining the input-output data from the experimental work. The input-output data validation outcome reveals a best-fit percentage for openloop 88.91% and closed-loop 95.43%, as well as a small Root Mean Square Error (RMSE). This indicates a successful validation between the estimated model and the actual system due to a high degree of agreement. The open-loop and closedloop identification have proven successful as there is no noteworthy disparity in the outcomes. The closed-loop system can be applied to unstable systems and any potential system